PENGERTIAN PENGUKURAN EVALUASI DAN ASSESMEN SERTA TUJUAN DAN FUNGSI EVALUASI PEMBELAJARAN - Achmad Rasyid Ridha; Ikke Fitriana Nugrahini; Iftitah Amin Suryani (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Improving the quality of the assessment system is one of the initiatives aimed at improving education standards. A strong learning framework will produce high-quality education, encourage educators to develop effective teaching strategies, and inspire students to engage in their learning more effectively. Measurement, assessment, assessment and evaluation each have a different scope and focus. The method in this research is a literature study used to analyze the literature relevant to the research topic. This research does so by analyzing literature related to the concepts of measurement, evaluation and assessment in Islamic Religious Education. The scope of assessment is shorter and usually only limited to one element, such as student achievement, student activeness and so on. In addition, assessments are conducted and used by individuals involved or part of the system concerned. Evaluation is broader and covers all components of the system, such as the education system, curriculum and learning. This can be done by internal and external evaluation. Basically, student learning outcomes consist of three domains: cognitive, affective and psychomotor. It is expected that teachers can develop these areas well in every lesson. Evaluation activities are carried out to determine the development of these three areas.